Berryman at letters. - Logan, William (New Criterion, 2022)
The article focuses on the life and works of poet John Berryman. It mentions that the poet wrote his mother, appeared as a member of the Ku Klux Klan with a "cringing submissive black slave" on a chain. It also mentions that he won a fellowship to study at Cambridge and there immersed himself neck deep in literature.